Fetal Survival in Second-trimester Termination of Pregnancy Without Feticide. Issue 3 (September 2018) - Springer, S.; Gorczyca, M.E.; Arzt, J.; Pils, S.; Bettelheim, D.; Ott, J.
Abstract : ( Obstet Gynecol 2018;131:575–579) The recommendations of the Society of Family Planning and guidelines of the Royal College of Obstetricians and Gynaecologists are that, in cases of late termination of pregnancy, feticide should be offered beyond 22 weeks of gestation to ensure stillbirth. However, data on live birth rates and survival times after pregnancy between 20 0/7 and 24 0/7 weeks of gestation are scarce and contradictory. In the present study, the authors reported on their own experience with termination of pregnancy procedures between 20 0/7 and 24 0/7 weeks of gestation not preceded by feticide; they evaluated the live birth rate and in cases of live birth, the duration of neonatal survival.